Analisis Perubahan Sikap Cinta Tanah Air dan Pancasila Siswa Pasca Pembelajaran Anti-Radikalisme di Sekolah Menengah Atas Negeri di Hulu Sungai Utara - Barkatillah (CV Putra Publisher, 2024)
This research aims to analyze changes in students' attitudes towards patriotism and Pancasila after anti-radicalism learning at State High Schools in Hulu Sungai Utara. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews and document analysis. The data sources in this research are principals of State Senior Secondary Schools and teachers, as well as students. The results of the research showed that there were positive changes in students' attitudes towards patriotism and Pancasila after participating in anti-radicalism learning. Factors that influence this change in attitude include the quality of learning materials, interactive teaching methods, and the role of teachers as learning facilitators. This research contributes to the development of anti-radicalism curriculum and learning strategies in schools in the area.